2016
DOI: 10.1093/jac/dkw200
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamics of carbapenems for the treatment ofPseudomonas aeruginosaventilator-associated pneumonia: associations with clinical outcome and recurrence

Abstract: Objectives: This study was designed to evaluate the pharmacodynamics of doripenem, imipenem and meropenem as a predictor of clinical success, mortality, 28 day recurrence and development of resistance in patients treated for Pseudomonas aeruginosa ventilator-associated pneumonia (VAP). Patients and methods:Previously published demographic and outcome data derived from patients treated for P. aeruginosa VAP with doripenem, imipenem or meropenem were utilized. Patient-specific data were used in conjunction with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 19 publications
3
21
0
Order By: Relevance
“…The pharmacodynamic threshold for meropenem is 40% f T > MIC [14]. Higher f T > MIC thresholds have been observed in human studies [26, 27], but applying more aggressive meropenem targets would not have resulted in different observations. Among these four patients who were unable to achieve optimal meropenem f T > MIC, all achieved a positive microbiological response, and 3 (75%) achieved a positive clinical response.…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacodynamic threshold for meropenem is 40% f T > MIC [14]. Higher f T > MIC thresholds have been observed in human studies [26, 27], but applying more aggressive meropenem targets would not have resulted in different observations. Among these four patients who were unable to achieve optimal meropenem f T > MIC, all achieved a positive microbiological response, and 3 (75%) achieved a positive clinical response.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, current knowledge on PK/PD targets for meropenem in heterogeneous ICU populations is limited, and a PK/PD target for this special patient population has not been derived yet. In relation to other PK/PD targets derived for meropenem in diverse clinical studies (e.g., 19.2%T >MIC and 47.9%T >MIC [ 21 ], 54%T >MIC [ 19 ] and 76-100%T >MIC [ 20 ]), the two PK/PD targets selected for our analysis were at the upper end (i.e., stricter). The selection of the higher targets seemed reasonable, given (1) limited knowledge on an adequate PK/PD target for heterogeneous ICU populations and (2) the high severity of illness (median APACHE II first study day 27) and the high proportion of patients with transplants (~58%) in the evaluated population.…”
Section: Discussionmentioning
confidence: 99%
“…As a β-lactam antibiotic, meropenem shows time-dependent activity; that is, its antibacterial activity is linked to the percentage of time that meropenem concentrations exceed the MIC value of a pathogen (%T >MIC ) [ 18 ]. The attainment of the pharmacokinetic/pharmacodynamic (PK/PD) index %T >MIC has been associated with clinical success in patients treated with meropenem [ 19 21 ]. For example, Ariano et al demonstrated that the probability of clinical response was 80% when %T >MIC was 76–100 in febrile neutropenic patients with bacteraemia but only 36% when %T >MIC was between 0 and 50 [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, previous studies suggest that 100% f T>MIC, or even 100% f T>4×MIC, may be considered in critically ill patients . However, a recently published study evaluated the pharmacodynamics of carbapenems in ventilator‐associated pneumonia caused by P aeruginosa . Classification and regression tree (CART) analysis identified that clinical success was associated with 19.2% f T>MIC, and ICU survival was associated with 47.9% f T>MIC …”
Section: Discussionmentioning
confidence: 99%